2002
DOI: 10.1002/jmri.10193
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the water resonance in small voxels in rat brain detected with high spectral and spatial resolution MRI

Abstract: Purpose: To acquire high spectral and spatial resolution (HiSS) MR images of the water resonance in rat brain, evaluate the lineshape of the water resonance in small voxels, and compare images derived from HiSS data with conventional images. Materials and Methods:Spectroscopic images of rat brain were obtained at 4.7 Tesla using phase encoding gradients only. Spectral resolution in each voxel was ϳ8 Hz and bandwidth was 1000 Hz. Spatial resolution was ϳ250 microns in 1-mm slices. Images were synthesized to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Each 4D complex array (k x × k y × k z × t) was Fourier transformed in all dimensions to produce three spatial dimensions and one spectral dimension (x × y × z × υ). For the complex spectrum, υ, spectral ghosting was corrected at each point (x, y,z), 43 an improved estimate of the frequency of the water peak was determined, 44 and real and imaginary components were phased to produce pure absorption and dispersion spectra. Spectra were phased using conventional techniques.…”
Section: C Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each 4D complex array (k x × k y × k z × t) was Fourier transformed in all dimensions to produce three spatial dimensions and one spectral dimension (x × y × z × υ). For the complex spectrum, υ, spectral ghosting was corrected at each point (x, y,z), 43 an improved estimate of the frequency of the water peak was determined, 44 and real and imaginary components were phased to produce pure absorption and dispersion spectra. Spectra were phased using conventional techniques.…”
Section: C Data Processingmentioning
confidence: 99%
“…Because of the voxel-by-voxel improved estimation of the peak location 44 in the spectral processing described above, B 0 maps were produced with greater precision than the nominal spectral resolution of the raw data.…”
Section: C Data Processingmentioning
confidence: 99%
“…It is equivalent to a Lorentzian shape in the frequency domain. Experimental results on animal models at high magnetic field, [1][2][3][4] however, suggest that the water resonance from some of the voxels exhibits nonLorentzian behavior, such as split peaks. Such phenomena are related to the heterogeneity in water composition inside the voxels, owing to subvoxelar tissue/vascular compartmentation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It has been demonstrated that decomposition of different water spectral components using high-resolution echo-planar spectroscopic imaging (EPSI) can improve the contrast of structural imaging and enhance the sensitivity in delineating lesions after administrating contrast media. 3,4,8,9 It is a logical extension to explore the usefulness of the high-resolution EPSI technique in human brain at clinical field strength. A number of recent fMRI studies have reported the observation of non-Lorentzian MR signal changes in the brain during functional tasks.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] For example, deoxyhemoglobin in small venules within an image voxel can produce resolved components of the water signal. [28][29][30] In such cases, destructive interference between the various components of the water resonance causes signal loss and distortion in conventional MRI where FID data are used (i.e. either single or multiple echoes).…”
Section: Discussionmentioning
confidence: 99%